Η ταυτότητα της Οφιτικής Ποντιακής: Μια γλωσσολογική μελέτη των πηγών και των ομιλητών της - Ρεβυθιάδου Ανθή; Σπυρόπουλος Βασίλειος; Κακαρίκος Κωνσταντίνος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2011)
Ofitika Pontic is a Greek dialect of the Pontic dialect group which is currently spoken in a few isolated pockets in Northern Greece by Pontian Greeks who originate from the of area, and also in about thirty villages in the provinces of of and Caykara in Turkey. The present study constitutes a structured documentation of Ofitika Pontic based on the outcomes of: (a) archival research a t the Taylor Bodleian Slavonic & Modern Greek Library of Oxford, the Research Centre for Modern Greek Dialects of the Academy of Athens and other specialized libraries in Greece and abroad, and (b) a fieldtrip to the village of Nea Trapezounta (prefecture of Pieria), which is predominantly inhabited by of is Pontians and their descendants. This study presents the basic typological characteristics of Ofitika Pontic at all grammatical levels (phonology, morphology and syntax) as these are revealed from the comparative study of the few existing (published and unpublished) grammatical descriptions of the dialect in question as well as the elaborate study of written Ofitika Pontic documents such as work logs, sayings, folk stories and narratives, cooking recipes, etc. The results of the archival and documentary research are further complemented with the findings of the research on the spoken material collected during the fieldwork in the village of Nea Trapezounta.